1996
DOI: 10.1063/1.361220
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of surface and bulk defects in p -GaSb by hydrogenated amorphous silicon treatment

Abstract: Passivation of point and extended defects in GaSb has been observed as a result of hydrogenated amorphous silicon ͑a-Si:H͒ treatment by the glow discharge technique. Cathodoluminescence ͑CL͒ images recorded at various depths in the samples clearly show passivation of defects on the surface as well as in the bulk region. The passivation of various recombination centers in the bulk is attributed to the formation of hydrogen-impurity complexes by diffusion of hydrogen ions from the plasma. a-Si:H acts as a protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…The 793 meV emission corresponds to the GaSb band edge transition, while we attribute the 730 meV band, which is observed in Te-doped crystals, to a Te-complex defect. Previous luminescence works on Te-doped GaSb [4,[14][15][16] have attributed a PL or a CL band peaked at different positions in the range from 730 meV to 746 meV, to the deep centre V Ga Ga Sb Te Sb proposed by Lebedev and Strel'nikova [17]. In the low temperature PL work of Iyer et al [14], transitions involving two Te-related acceptor levels, separated by 15 meV, were reported and it was concluded that the relative dominance of each transition depends on the We suggest that the band at about 760 meV, which has a much lower intensity than the two other bands, is the so called band B, previously reported to peak at about 756 meV [4,15] which is associated with the complex V Ga Ga Sb V Ga arising from an excess of Ga vacancies [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…The 793 meV emission corresponds to the GaSb band edge transition, while we attribute the 730 meV band, which is observed in Te-doped crystals, to a Te-complex defect. Previous luminescence works on Te-doped GaSb [4,[14][15][16] have attributed a PL or a CL band peaked at different positions in the range from 730 meV to 746 meV, to the deep centre V Ga Ga Sb Te Sb proposed by Lebedev and Strel'nikova [17]. In the low temperature PL work of Iyer et al [14], transitions involving two Te-related acceptor levels, separated by 15 meV, were reported and it was concluded that the relative dominance of each transition depends on the We suggest that the band at about 760 meV, which has a much lower intensity than the two other bands, is the so called band B, previously reported to peak at about 756 meV [4,15] which is associated with the complex V Ga Ga Sb V Ga arising from an excess of Ga vacancies [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…Our recent studies clearly demonstrated the effectiveness of a-Si:H treatment in achieving bulk passivation due to plasma hydrogen in addition to a defect-free surface terminated by a-Si:H. 263,268,269 Efficient passivation of point and extended defects can be carried out by a-Si:H. Typical depth resolved CL images recorded before and after passivation are shown in Fig. 44.…”
Section: A-si:h Passivationmentioning
confidence: 86%
“…[260][261][262] The problem of surface degradation can be solved by a protective cap layer like a-Si:H on the sample surface during the plasma exposure which is permeable to hydrogen. 263 The details of various passivation treatments on GaSb carried out hitherto are discussed below.…”
Section: Surface and Bulk Defect Passivationmentioning
confidence: 99%
“…Recently, many different technologies for GaSb passivation have received much attention due to the prominent improvement of electrical and optical characteristics. [2][3][4][5][6][7][8][9][10][11][12][13] Among these, sulfuring GaSb with a (NH 4 ) 2 S solution is a noteworthy one that has the merits of thermal stability and simple treatment. However, it is not yet known how the electronic properties of sulfured GaSb surfaces can be improved.…”
Section: Introductionmentioning
confidence: 99%